Phenotypic genetic and cytogenetic characterization of Ghumusari cattle of Odisha- a newly accredited breed - S.K Das; B. Prakash; Sethi, B.P (Journal of Livestock Biodiversity, 2025)
Ghumusari cattle are raised in the eastern province of Odisha of India by farming families in mixed faming system. The breed numbers are declining very fast, due to non availability of quality bulls in the native tract. Animals are small in size with mature body weight of 170-210 kg for bulls and 140-185 kg for cows, quite uniform in colour (white/grey) and body conformation, have moderate dewlap and reduced umbilical folds and relatively large hump in males. Animals are heat tolerant, sustain on low quality feed intake under high ambient temperatures, resistant to many diseases prevailing in the region and cows have good mothering ability. Productivity of the breed in terms of milk is low but bullocks are very good draft animals. Reproduction performance excels like that of other small sized indigenous zebu cattle breeds. Cytogenetic profiling revealed their typical Bos indicus status (acrocentric Y chromosome). Genetic characterization based on 21 FAO-recommended microsatellite markers demonstrated high genetic variability prevailing in Ghumusari cattle population. Efforts should be made to stop the decline in the breed numbers and to conserve the breed as an asset for production under harsh environment of the native tract.